Nasogastric Tube Placement and Verification in Children: Review of the Current Literature. (15th April 2014) - Irving, Sharon Y.; Lyman, Beth; Northington, LaDonna; Bartlett, Jacqueline A.; Kemper, Carol; ,; Alden, Tor; Avram, Debra Ben; Coghill, Tim; Fanta, Sarah; Flack, Marilyn; Goday, Praveen; et al.
Abstract : Placement of a nasogastric enteral access device (NG‐EAD), often referred to as a nasogastric tube, is a common practice and largely in the domain of nursing care. Most often an NG‐EAD is placed at the bedside without radiographic assistance. Correct initial placement and ongoing location verification are the primary challenges surrounding NG‐EAD use and have implications for patient safety. Although considered an innocuous procedure, placement of an NG‐EAD carries risk of serious and potentially lethal complications. Despite acknowledgment that an abdominal radiograph is the gold standard, other methods of verifying placement location are widely used and have success rates from 80% to 85%. The long‐standing challenges surrounding bedside placement of NG‐EADs and a practice alert issued by the Child Health Patient Safety Organization on this issue were the stimuli for the conception of The New Opportunities for Verification of Enteral Tube Location Project sponsored by the American Society for Parenteral and Enteral Nutrition. Its mission is to identify and promote best practices with the potential of technology development that will enable accurate determination of NG‐EAD placement for both the inpatient and outpatient pediatric populations. This article presents the challenges of bedside NG‐EAD placement and ongoing location verification in children through an overview of the current state of the science. It is important for all healthcare professionals to be knowledgeable about the current literature, to be vigilant for possible complications, and to avoid complacency with NG‐EAD placement and ongoing verification of tube location.